Microplastics in feed cause sublethal changes in the intestinal microbiota and a non-specific immune response indicator of the freshwater crayfish Procambarus clarkii (Decapoda: Cambaridae) - Guillén-Watson, Rossy; Arias-Andres, Maria; Rojas-Jimenez, Keilor; Wehrtmann, Ingo S. (Frontiers in Microbiology, 2023)
Microplastics (MP) are a hazardous pollutant of global concern that threatens aquatic ecosystems and public health. We used the invasive, cosmopolitan, and environmentally versatile red swamp crayfish Procambarus clarkii as a model to study the effects of MP on the intestinal microbiome. Crayfish collected from the environment were compared with specimens exposed to recycled Polyethylene terephthalate (rPET) MP in feed (30%) for 96 hours in the laboratory and a control group. We analyzed the 16S rRNA of the intestinal bacteria by PCR-DGGE and high-throughput sequencing.1 MP exposure caused dysbiosis of the intestinal microbiota, with an increase in Alphaproteobacteria and Actinobacteria. We detected higher abundance of opportunistic genera such as Klebsiella, Acinetobacter, Hydromonas, Pseudomonas, Gemmobacter, and Enterobacter on MP fed organisms.Moreover, MP exposure reduced the abundance of Clostridia and Bateroidetes, which are important for immune system development and pathogen prevention. Furthermore, MP exposure decreased the phenoloxidase (PO) immune response in crayfish. There was a significant difference in the richness of intestinal bacterial communities after consumption of food contaminated with MP, likely increasing the abundance of opportunistic bacteria in the intestinal microbiota. Our results suggest that MP alter the gut microbial composition and impair the health of P. clarkii.